THE USE OF REFLECTION FOR SPIRITUAL CARE LEARNING IN CLINICAL EDUCATION: A PILOT STUDY - Gisella Anastasia; Yoyo Suhoyo; Prattama Santoso Utomo; Doni Widyandana (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2020)
Background: Indonesian society assume spirituality as an important aspect in life especially in sickness. Spiritual care can restore patients’ quality of life by providing them comfort, strength, and compassion. Because lack of education about spiritual care, doctors often feel not fully equipped. Reflection has proven to increase awareness of spiritual care, but the impact of this method still needs further research. This study aims to explore the impact of reflection on student awareness about spiritual care.Methods: This study used Interpretative Phenomenological Analysis with reflective writing and in-depth interview. Nine clinical medical students divided into four groups which was facilitated by clinical teacher. Intervention were three reflective writings interspersed with two small group discussion. The writings were analyzed using Transtheoretical Model to identify behavioral change then content analysis for the transcript to explore the study’s impact and the feasibility.Results: Five students increased their awareness because clinical experience, time-management, writing volume, and reflective thinking. Three students increase faster because learning from peers, engage with patient, and role-model. Two students increase slower because lack understanding of reflection and incorrect facilitators’ feedbacks. Two students stable because lack understanding of discussion and low engagement with patient. One student experienced a decrease because lack of task-commitment and interest. One student did not get awareness because difficulty interpreting emotions.Conclusion: Reflection method can be used to teach spiritual care to clinical medical students by considering several factors that might play a role. Further research with improvement to the method is still needed. Keywords: Spiritual care; spirituality; reflection; clinical medical student